1988
DOI: 10.1029/jd093id10p12569
|View full text |Cite
|
Sign up to set email alerts
|

Possible contribution of N2O5 scavenging to HNO3 observed in winter stratiform cloud

Abstract: During a winter field study in early 1984, the concentrations of NO3−, SO4=, and H+, measured in cloud water samples collected in the bases of deep stratiform clouds and in the aerosol and gas phases below cloud, suggested a substantial enhancement of NO3− in the cloud water samples for 8 of 12 days. For these 8 days, variations in cloud water NO3−/SO4= were associated with an excess H+/SO4= in the cloud water, indicating HNO3. For the conditions of study, which included subfreezing temperatures and weak solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…At the pdD sampling site, since the origin of the air masses is variable with high nitrate fractions for polluted air masses, this conclusion cannot be applied. Several values of this ratio reported elsewhere for cloud water samples were below 1 (Baltensperger et al, 1998;Bridges et al, 2002) but the observation of elevated NO − 3 relative to SO 2− 4 in cloud water has been also reported in other studies Hayden et al, 2008;Hill et al, 2007;Leaitch et al, 1986;Lee et al, 2012). This could be related to high NO x emission and the predominance of nitrate over sulfate in the acidification of aerosols.…”
Section: Inorganic Ionsmentioning
confidence: 53%
See 1 more Smart Citation
“…At the pdD sampling site, since the origin of the air masses is variable with high nitrate fractions for polluted air masses, this conclusion cannot be applied. Several values of this ratio reported elsewhere for cloud water samples were below 1 (Baltensperger et al, 1998;Bridges et al, 2002) but the observation of elevated NO − 3 relative to SO 2− 4 in cloud water has been also reported in other studies Hayden et al, 2008;Hill et al, 2007;Leaitch et al, 1986;Lee et al, 2012). This could be related to high NO x emission and the predominance of nitrate over sulfate in the acidification of aerosols.…”
Section: Inorganic Ionsmentioning
confidence: 53%
“…The potential sources of nitrate, sulfate and ammonium in cloud water are multiple and include particles (ammonium sulfate and ammonium nitrate particles) and gases (from SO 2 , HNO 3 , NH 3 , N 2 O 5 ) (Leaitch et al, 1988;Sellegri et al, 2003). The concentrations of ammonium, nitrate and sulfate are significantly correlated within each category of air mass (R varies between 0.64 to 0.94, n = 6 to 70).…”
Section: Inorganic Ionsmentioning
confidence: 99%
“…In the concentrated volume of the cloud droplets, HNO 3 can react with NH 3 , also absorbed from the gas phase, or with alkaline compounds that may enter the droplets via nucleation scavenging. Also, clouds change the actinic radiation both in and around them that can promote or inhibit the formation of N 2 O 5 [ Leaitch et al , 1988]. In turn, nitrate particles are effective cloud condensation nuclei, and therefore can contribute to the indirect effects of aerosols on climate [ Intergovernmental Panel on Climate Change , 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The data presented include only measurements taken within daytime hours. The presence of N 2 O 5 will be less likely than at nighttime; however, inside clouds the actinic radiation can be significantly reduced, so potential contributions from gas‐phase N 2 O 5 cannot be ruled out [ Leaitch et al , 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Leaitch et al (1988) studied the dissolution of N 2 O 5 in cloud droplets by using a Lagrangian chemical model with winter conditions in northeastern region of the United States and compared the resulting NO 3 − content in cloud water with measured values. They showed that the mean production rate of HNO 3 via cloud scavenging is also much more efficient than homogeneous N 2 O 5 hydrolysis, which was observed by Colvile et al (1994) as well.…”
Section: Model Representation Of N 2 O 5 Uptakementioning
confidence: 99%